Are health professionals' perceptions of patient safety related to figures on safety incidents?. Issue 5 (29th July 2012) - Martijn, Lucie; Harmsen, Mirjam; Gaal, Sander; Mettes, Dirk; van Dulmen, Simone; Wensing, Michel
Abstract: Objective: The study aims to explore whether health care professionals' perceptions of patient safety in their practice were associated with the number of patient safety incidents identified in patient records. Setting: Seventy primary care practices of general practice, general dental practice, midwifery practices and allied health care practices were used in the study. Methods: A retrospective audit of 50 patient records was performed to identify patient safety incidents in each of the practices and a survey among health professionals to identify their perceptions of patient safety. Results: All health professions felt that 'communication breakdowns inside the practice' as well as 'communication breakdowns outside the practice' and 'reporting of patient safety concerns' were a threat to patient safety in their work setting. We found little association between the perceptions of health professionals and the number of safety incidents. The only item with a significant relation to a higher number of safety incidents referred to the perception of 'communication problems outside the practice' as a threat to patient safety. Conclusions: This study indicates that the assessment of professionals' perceptions may be complementary to observed safety incidents, but not linked to an objective measure of patient safety.